Thian's Proposed History of Confederate Treasury (Quarterly Journal of Economics, 1890)
Journal Article Thian's Proposed History of Confederate Treasury Get access The Quarterly Journal of Economics, Volume 4, Issue 3, April 1890, Pages 316–317, https://doi.org/10.1093/qje/4.3.316-a Published: 01 April 1890